+0

# e^17.3 * x / (x + 237.3) = 0.013 * (x + 273.2)

+5
63
2

e^17.3 * x / (x + 237.3) = 0.013 * (x + 273.2)

Guest Feb 27, 2017
Sort:

#1
+89752
0

e^17.3 * x / (x + 237.3) = 0.013 * (x + 273.2)

$$\frac{e^{17.3} \times x }{ (x + 237.3) }= 0.013 (x + 273.2)\\ e^{17.3} \times x = 0.013 (x + 273.2)(x + 237.3) \\$$

Just expand it all out, take it all to one side ie make =0

then solve using the quadratic formula :)

Melody  Feb 27, 2017
#2
0

Solve for x:
0.013 (x + 237.3) (x + 273.2) = 3.26058×10^7 x

Expand out terms of the left hand side:
0.013 x^2 + 6.6365 x + 842.795 = 3.26058×10^7 x

Subtract 3.26058×10^7 x from both sides:
0.013 x^2 - 3.26058×10^7 x + 842.795 = 0

x = (3.26058×10^7 ± sqrt((-3.26058×10^7)^2 - 4×0.013×842.795))/0.026 = (3.26058×10^7 ± sqrt(1.06314×10^15))/0.026 = (3.26058×10^7 ± 3.26058×10^7)/0.026 = 1.25407×10^9 ± 1.25407×10^9:
x = 2.50814×10^9 or x = 0.0000259338

0.013 (x + 237.3) (x + 273.2) ⇒ 0.013 (237.3 + 0.0000259338) (273.2 + 0.0000259338) ≈ 842.795
3.26058×10^7 x ⇒ 3.26058×10^7 0.0000259338 ≈ 845.59:
So this solution is incorrect

0.013 (x + 237.3) (x + 273.2) ⇒ 0.013 (237.3 + 2.50814×10^9) (273.2 + 2.50814×10^9) ≈ 8.17797×10^16
3.26058×10^7 x ⇒ 3.26058×10^7 2.50814×10^9 ≈ 8.17797×10^16:
So this solution is incorrect

All the solutions are incorrect:
Answer: | NO SOLUTIONS!!

Guest Feb 27, 2017

### 17 Online Users

We use cookies to personalise content and ads, to provide social media features and to analyse our traffic. We also share information about your use of our site with our social media, advertising and analytics partners.  See details